1998
DOI: 10.1017/s0960258500004025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dormancy-breaking chemicals on ABA levels in barley grain embryos

Abstract: The endogenous ABA contents of dormant and nondormant barley grains were determined following application of different compounds to break dormancy. The chemicals used for breaking of dormancy in intact dormant grains were weak and strong acids, alcohols, hydrogen peroxide, cyanide, nitrate, salicylic acid, gibberellic acid and fusicoccin. The dormancy-breaking compounds could be classified into two major groups: compounds that caused a decrease in endogenous ABA (class I) and compounds which did not affect end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 27 publications
7
57
0
Order By: Relevance
“…In contrast, imbibition on peroxide resulted in the simultaneous development of the seedling shoot and root system (Table 2), and imbibition of switchgrass seeds on ABA + H 2 O 2 resulted in a signiWcant enhancement in shoot and root growth as compared to seeds maintained on ABA alone. These data demonstrated that for switchgrass seeds, addition of H 2 O 2 could largely overcome the negative eVects of ABA, possibly by swamping ABA-dependent signaling, as has been suggested for barley (Wang et al 1998). Conceivably, exogenous peroxide could act through several diVerent routes in signiWcantly promoting switchgrass seed germination.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In contrast, imbibition on peroxide resulted in the simultaneous development of the seedling shoot and root system (Table 2), and imbibition of switchgrass seeds on ABA + H 2 O 2 resulted in a signiWcant enhancement in shoot and root growth as compared to seeds maintained on ABA alone. These data demonstrated that for switchgrass seeds, addition of H 2 O 2 could largely overcome the negative eVects of ABA, possibly by swamping ABA-dependent signaling, as has been suggested for barley (Wang et al 1998). Conceivably, exogenous peroxide could act through several diVerent routes in signiWcantly promoting switchgrass seed germination.…”
Section: Discussionsupporting
confidence: 56%
“…1; Tables 1and 2) show that treatment with H 2 O 2 as an exogenous source of ROS signiWcantly promotes seed germination in several warm-season C 4 -grasses such as switchgrass, big bluestem and indiangrass. Treating seeds with H 2 O 2 has been shown to promote germination in several other species, including zinnia (Zinnia elegans L.) (Ogawa and Iwabuchi 2001), rice (Oryza sativa L.) (Naredo et al 1998), wheat (Triticum aesitvum L.) (Wahid et al 2007) and barley (H. vulgare L.) (Wang et al 1998). What has not been explored in warm-season grasses is the relationship between H 2 O 2 , NO and ABA during seed germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in ABA has been observed in Arabidopsis seeds in response to a heat treatment at 34 °C (Toh et al 2008). A similar decrease in ABA was observed in Hordeum distichon cv Triumph seeds after applying a treatment with H 2 SO 4 to break dormancy (Wang et al 1998).…”
Section: Mobilization Of Reservessupporting
confidence: 79%
“…Exogenous H 2 O 2 stimulates the germination of dormant seeds of barley, Fontaine et al 1994; rice, [37] apple [38] and tomato [20]. Treatment of dormant barley seeds with hydrogen peroxide results in a decrease in endogenous ABA level [39] and alleviation of apple embryo dormancy by cyanide induces a simultaneous increase in H 2 O 2 level and decrease in ABA content [38]. H 2 O 2 promoted seed germination in a dose-dependent manner as did respiratory inhibitors, indicating that H 2 O 2 itself possibly promotes seed germination rather than O 2 [40].…”
Section: Resultsmentioning
confidence: 99%